Niger Delta Poetry and Traumatic Inscriptions: A Reading of Sophia Obi’s Tears in a Basket - Esamagu, Blessing Ochuko (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Environmental degradation, beyond being a global phenomenon, is fast becoming a major cause of concern in Africa with severe impacts on humans and non-humans. This mindless exploitation of natural resources, particularly in the Niger Delta region of Nigeria, does not only adversely affect aquatic and terrestrial habitats, making them endangered species, but also leaves scathing impacts on humans, which range from physical to psychological. Previous studies have largely focused on analysing the destructive consequences of environmental degradation on non-humans and the effects on the material well-being of humans in Sophia Obi’s Tears in a Basket. However, this study argues that the destruction of the environment in the Niger Delta region directly affects the psychological and mental health of the inhabitants in the affected communities, causing trauma. Therefore, this study is a critical reading of Sophia Obi’s Tears in a Basket as a narrative of trauma. The study adopts ecocriticism (the study of nature in literature), Stef Craps’ model of trauma theory, which redefines trauma to include unending, quotidian kinds of brutality that befall persons in lower factions, and engages Rob Nixon’s concept of “slow violence”, which focuses on the accretive, cumulative impact of environmental degradation on marginalised communities. The text is subjected to literary and critical textual analysis to examine its preoccupation with the subject of trauma, through the prisms of individual and collective suffering among the Niger Delta people. The study establishes that environmental degradation possesses the potential to generate trauma.